2020
DOI: 10.7759/cureus.10918
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Dexamethasone and Methylprednisolone in Improving PaO2/FiO2 Ratio Among COVID-19 Patients

Abstract: Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the reason for the global pandemic that started from Wuhan, China, in December 2019, known as coronavirus diseases 2019 (COVID-19). Acute respiratory distress syndrome happened in COVID-19 not just because of uncontrolled viral replication but also because of an uncontrolled immune reaction from the host. That's why antiviral and anti-inflammatory treatments have become an increasing concern for clinicians. Methods A retrospective qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 14 publications
4
23
1
4
Order By: Relevance
“…At the beginning of the outbreak in Arequipa (March-April 2020), Hydroxychloroquine with or without lopinavir / ritonavir or azithromycin was used as a standard treatment and according to the best evidence at that time as a therapy against SARS-CoV-2 according to national guidelines [1] and the medical literature available [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the beginning of the outbreak in Arequipa (March-April 2020), Hydroxychloroquine with or without lopinavir / ritonavir or azithromycin was used as a standard treatment and according to the best evidence at that time as a therapy against SARS-CoV-2 according to national guidelines [1] and the medical literature available [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding agents with direct action against the virus, initial hopes focused on remdesivir, Hydroxychloroquine, lopinavir / ritonavir and interferon-β. Of these agents, only remdesivir appears to have any favorable action against COVID-19 [4][5][6][7][8][9][10]. In contrast, various studies have shown the lack of efficacy of the other schemes [11][12][13][14][15][16][17][18][19][20].…”
Section: Textomentioning
confidence: 99%
See 1 more Smart Citation
“… The early-stage use of a combination of favipiravir and methylprednisolone in severe cases can achieve a favorable clinical outcome 25 Alejandro Rodríguez-Molinero/Spain Cohort study 418 Steroids/No steroids 65.4 56.9% COVID- 19 patients with pulmonary involvement 6 (8.1%)/10(13.2%) Methylprednisolone 1 mg/kg/day or dexamethasone 20–40 mg/day The mortality can not been analysed due to the low number of events. There is no benefit in the use of glucocorticoids in terms of lung function or time to discharge 26 Yan Hu/China Single-center study 308 Steroids/No steroids 54 (44–63)/48 (39–60) 47.2%/46.7% COVID- 19 patients with pulmonary involvement None Equivalent of methylprednisolone 0.75–1.5 mg/kg/d) Glucocorticoid therapy did not significantly influence the clinical course, adverse events nor the outcome of COVID-19 pneumonia 27 Muhammad A. Rana/PAK Retrospective quasi-experimental study 60 Dexamethasone/Methylprednisolone 53.8/53.9 66.7%/70% Patients treated in HDU/ICU and had been on bi-level positive airway pressure. Not mentioned Dexamethasone 8 mg BID/Methylprednisolone 40 mg BID; 8 days Dexamethasone is more effective in improving the P/F ratio in COVID-19 patients compared to methylprednisolone 28 Marla J Keller/UAS Observational study 1806 Steroids/No steroids 61.7 ± 15.9/62.3 ± 17.9 49.3%/46.3% COVID-19 patients Glucocorticoid increased mortality of patients with CRP< 10 mg/dL Early glucocorticoids (within 48 hours of admission) Choosing the right patients is critical to maximize the likelihood of benefit and minimize the risk of harm 29 Hong-Ming Z...…”
Section: Pros and Cons Of Glucocorticoid Therapymentioning
confidence: 99%
“…Although the studies that evaluated the use of HCQ have not demonstrated its effectiveness as a protective or therapeutic agent 21 , its use also seems to have no association with worse outcomes 22,23 . Some studies using CS in the acute phase of COVID-19 have also shown their effectiveness in controlling inflammation markers, particularly in cases of ARDS 24,25 . Thus, the association of worse outcomes with intrahospital use of CS and HCQ could be related to its use in more severe patients, perhaps late, in an attempt to improve the patient's condition, when there was little knowledge about the treatment of COVID-19.…”
Section: This Study Is Supported By Grants From the National Council mentioning
confidence: 99%